Skeletal blood flow in metabolic disorders of the skeleton. - Green, JR; Reeve, J; Tellez, M; Veall, N; Wootton, R (1987)
Results are presented of measurements of skeletal blood flow made in 80 patients with painful benign or malignant diseases of the skeleton, excluding patients with Paget's disease. In crush fracture osteoporosis, total bone blood flow was slightly lower than normal although skeletal perfusion was normal. High values of bone blood flow were seen in 14/20 patients with osteomalacia and 3/12 patients with primary hyperparathyroidism. Very high values, comparable to those seen in the most severely affected patients with Paget's disease, were seen in polyostotic fibrous dysplasia, 2 out of 4 cases of Engelmann's disease and 1 out of 3 cases of renal osteodystrophy. Results were less elevated in myositis ossificans, secondary skeletal involvement with breast and prostatic carcinomata, myelomatosis and sympathetic osteodystrophy.